Nieufny i oburzeni. Polemiki wokół Szeptem Kazimiery Iłłakowiczówny - Marzec, Lucyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This article discusses the literary dispute over Kazimiera Iłłakowiczówna’s poetry collected in the Szeptem volume (1966). The dispute started with an ironic review by a young literary critic, Stanisław Barańczak, in the “Nurt” magazine published in Poznań. The article’s author interprets three aspects of the dispute: its legend-creating impact on Iłłakowiczówna as a literary institution, its destructive nature against Iłłakowiczówna as a canonical poet and the dispute’s status in the literary circles of the 1960s. The article provides evidence that Barańczak’s pamphlet hit the poetics and legend of Iłłakowiczówna; what is more, it triggered off a self-repair mechanism of the canon, reinforcing and sealing it from the pressure exerted by the young poets and critics in the late 1960s and the early 1970s. This mechanism, ephemeral from the point of view of the dynamics of literary circles, ultimately carved in stone the legend of Iłłakowiczówna, preventing new interpretations of her poetry and biography.